Environmental heterogeneity and anthropic alterations in mangrove communities in the Southern Pacific of Mexic - Moreno-Martínez, Ameyali (2021)
[Introduction] The environmental heterogeneity of mangroves is consistently related to local biophysical and anthropic factors. Because these ecosystems are subject to different natural or anthropic pressures, understanding the effect of these management practices on their components is necessary to take action to increase their degree of resilience to extreme weather events. [Objective] This research was aimed at evaluating the environmental condition of 4 mangrove communities based on the study of soil and vegetation components, through a set of edaphic and dasometric properties, in the Northern area of the Coyuca Lagoon, Mexico. [Methodology] The selection of study and sampling sites considered their spatial representativeness, degree of alteration, and proximity to the coastline. Tree structure and biomass were characterized, and 30 cm-deep soil samples were taken for lab analysis. [Results] Forest inventory showed the presence of the Rhizophora mangle, Laguncularia racemosa, and Conocarpus erectus species, whose distribution is mainly related to the soil hydric regimen, pH, and salinity. Above-ground and soil carbon storage fluctuated between 41.5 and 165 Mg ha-1, being consistent with their degree of disturbance. [Conclusions] The main effects of the anthropic activities were partial loss of forest structure due to slash-and-burn, compaction of the top soil, resulting in increased apparent density and reduced carbon stored in biomass and soil.